Historia jednego motywu – rzecz o związkach biżuterii z architekturą - Wrześniak, Małgorzata (Załącznik Kulturoznawczy, 2023)
The hereby text is a short study on the relationship between architecture and jewellery. In the first part, it presents the history of occurrence of architectural forms in jewellery from antiquity to present day in the European culture. The second part delivers the examples of contemporary artefacts, particularly rings with microarchitecture. The analysis of the collected examples proves that architecture – its form, construction and detail − is a motive of decoration willingly used in jewellery design, often of a symbolic meaning related to the household or the temple (wedding rings, ritual rings). Nowadays, especially in the 21st century, microarchitecture in jewellery often emerges with reference to the place of origin, i.e. the famous buildingbeing, most frequently, the commemoration of a journey, able to bring back the memory of a visited city.The architectural jewellery, whose meanings and functions are the subject of the hereby study, has undergone many transformations throughout history. Even though it has transitioned from simple to complicated and decorative forms, from precious and rare to cheap and popular objects of mass production presenting the miniature replicas of buildings, the jewellery nearly always symbolises the city. Much less often the jewellery design occurs with reference to the metaphorical meanings of buildings as a representation of permanency (the tower in Alessandro Dari’s jewellery) or marital union (the house and the temple in Jewish rings).